Neonatal Parotitis: A case report - Nawal Khan; Asad Abdullah; Farhana Zafar (Journal of the Pakistan Medical Association, 2021)
The following is a case report of a 17-day old female baby, born at 35 weeks’ gestation, weighing 2.6 kilograms. She presented to us with reluctance to feed, swelling over the left side of her face and a fever documented at 102F, along with an erythematous, tender, localized swelling over the left pre-auricular region that measured 2 x 1.5cm in size. Diagnostic workup revealed ultrasound findings consistent with parotitis, however, her blood culture was negative. The patient was managed on antibiotics but subsequently, developed a nosocomial infection during her admission, which prolonged her hospital stay to a total of 16 days. Nevertheless, she had complete resolution of signs and symptoms on her follow-up visit. Continuous...